Determination of cefcapene acid by LCâMS and their application to a pharmacokinetic study in healthy Chinese volunteers - Hong-Fei Duan; Li Ding; Xiao-Bing Li; Lin-Lin Hu; Ai-Dong Wen; Ye Leng; Zhen Liu (Elsevier, 2013)
Simple, rapid and specific liquid chromatographyâmass spectrometry (LCâMS) methods have been developed and validated for the quantification of cefcapene acid in human plasma and urine. Plasma samples were simply pretreated with methanol for deproteinization. Urine samples were briefly diluted with methanolâwater (50:50, v/v), and centrifuged to remove large particles. Chromatographic separation was performed on a Hedera ODS-2 column. For the plasma assay, the isocratic mobile phase consisted of 35% solvent A (Methanol) and 65% solvent B (10Â mM ammonium acetate buffer solution containing 0.2% folic acid) with a flow rate of 0.3Â mL/min. For the urine assay, the isocratic mobile phase consisted of 30% solvent A (Methanol) and 70% solvent B (10Â mM ammonium acetate buffer solution containing 0.2% folic acid) with a flow rate of 0.3Â mL/min. The assays were linear over the concentration ranges of 0.03â5Â Î¼g/mL in plasma and 0.1â400Â Î¼g/mL in urine, and were successfully applied to a pharmacokinetic study after single and multiple oral administrations of cefcapene pivoxil hydrochloride tablets in healthy Chinese volunteers. Keywords: Cefcapene acid, Cefcapene pivoxil, LCâMS, Human plasma, Urine, Pharmacokinetics